Juridical Analysis of the Implementation of Buying and Selling Former Customary Land in Wajo Regency - Andi Baso Mappangile; Andi Suryaman Mustari Pide; Kahar Lahae (LEGAL BRIEF, 2022)
Regarding the buying and selling used customary land without signing in front of the Camat as the temporary PPAT that occurred in the Wajo area, this has certainly become a legal problem. This problem is related to the authentication of the land transaction deed as the principle of land registration at the National Land Agency of Wajo Regency. The research method in this study uses empirical legal research (law in action), which is to examine and analyze the workings of law in society, using a sociology of law approach. The legal sociology approach is an approach that analyzes how the reaction or interaction occurs when the norm system works in society. With the results of the study, although the signing of the deed of sale by the parties concerned, the seller, buyer and witnesses were not carried out before the authorized PPAT, in this case the PPAT of the Camat, if there was no legal problem (dispute) then the deed of sale and purchase was still considered as an authentic deed because physically in the form of the deed of sale there are signatures of the parties concerned, namely the seller, the buyer, the witnesses and the PPAT itself. The implementation of the sale and purchase of former property rights (custom) in Wajo Regency which is carried out before the Village Head is basically not in accordance with land law in Indonesia. This is because since the UUPA was enacted, only deeds made by authorized officials (PPAT) can be used as the basis for the transfer of land rights as stated in Article 37 paragraph (1) Government Regulation no. 24 Years l997.